Materials characterisation and mechanical properties of Cf-UHTC powder composites. Issue 4 (April 2019) - Rubio, V.; Binner, J.; Cousinet, S.; Le Page, G.; Ackerman, T.; Hussain, A.; Brown, P.; Dautremont, I.
Abstract: Ultra-high temperature ceramic composites based on carbon fibre, Cf, preforms impregnated with hafnium diboride, HfB2, powder and then densified with carbon by chemical vapour infiltration, CVI, have been mechanically tested to measure the room temperature flexural, interlaminar shear, compressive and tensile strengths. The latter was also measured at 1000 °C. All the composites suffered a degree of delamination during the different mechanical tests but the strength values obtained were at least equal to, or better than, those previously reported in the literature for ultra-high temperature ceramic (UHTC)-based composites. Importantly, in spite of the oxidation of the tensile samples tested at 1000 °C, similar tensile strength values were obtained at both temperatures, suggesting that the materials can resist elevated temperatures. The samples tested at higher temperature did show greater evidence of fibre pull out, possibly due to a weaker fibre-matrix interface as a result of oxidative degradation. The results also suggested that the 0° orientation plies in the Cf preform structure offered greater resistance to mechanical stresses; this suggests that composites can now be designed to offer even greater strength values.